Henry Clerval Scolding Victor Frankenstein: An autoethnographic poem about graduate students and their daemons - Henze, Adam David (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
This article explores the “daemons” that many university students face by exploring Mary Shelley’s Frankenstein in a creative way. Using a poetic method called “erasure,” the author of this article cut fragmented descriptions of Victor Frankenstein, and stitched them together to craft a poem about the need for self-care in the university setting. The poem includes a preface to provide some theoretical context and background information on Frankenstein.